2018
DOI: 10.1007/s12298-018-0543-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Brassinazole resistant (BZR) gene family and stress induced expression in Eucalyptus grandis

Abstract: Brassinosteroids (BRs) are a group of plant hormones which play a pivotal role in modulating cell elongation, stress responses, vascular differentiation and senescence. In response to BRs, BRASSINAZOLE-RESISTANT (BZR) transcription factors (TFs) accumulate in the nucleus, where they modulate thousands of target genes and coordinate many biological processes, especially in regulating defense against biotic and abiotic stresses. In this study, 6 BZR TFs of () from a genome-wide survey were characterized by seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(55 reference statements)
2
17
0
Order By: Relevance
“…In our study, six, eight, eight, twelve and thirteen BZR-coding protein sequences were identified in F.vesca , P. mume , P. persica , P. communis and P. bretschneideri , respectively ( Table S1 ). Compared with other gene families in the studied species, the BZR gene family is of relatively small size, which is consistent with the previous studies such as six, six, eleven and fifteen BZR genes in A. thaliana , E. grandis , Z. mays and B. rapa , respectively ( Saha et al, 2015 ; Fan et al, 2018 ; Manoli et al, 2018 ; Yu et al, 2018 ). Interestingly, the numbers of BZR genes have a certain degree of expansion in both P. communis and P. bretschneideri , when compared with those in F. vesca , P. mume and P. persica .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, six, eight, eight, twelve and thirteen BZR-coding protein sequences were identified in F.vesca , P. mume , P. persica , P. communis and P. bretschneideri , respectively ( Table S1 ). Compared with other gene families in the studied species, the BZR gene family is of relatively small size, which is consistent with the previous studies such as six, six, eleven and fifteen BZR genes in A. thaliana , E. grandis , Z. mays and B. rapa , respectively ( Saha et al, 2015 ; Fan et al, 2018 ; Manoli et al, 2018 ; Yu et al, 2018 ). Interestingly, the numbers of BZR genes have a certain degree of expansion in both P. communis and P. bretschneideri , when compared with those in F. vesca , P. mume and P. persica .…”
Section: Resultssupporting
confidence: 91%
“…As previously reported, the members of the BZR gene family were found to be involved in the regulation of various processes in plants, and the positive roles of the BZR genes in BR signal transduction have been well studied in plants, such as A. thaliana , Brassica rapa , Eucalyptus grandis and Zea mays ( Clouse et al, 1996 ; Li and Chory, 1997 ; Ye et al, 2010 ; Clouse, 2011 ; Saha et al, 2015 ; Fan et al, 2018 ; Manoli et al, 2018 ; Yu et al, 2018 ). However, no systematic, in-depth study of the BZR gene family has been reported in five Rosaceae species, including F. vesca , P. mume , P. persica , P. communis , and P. bretschneideri .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Specific primers of the EgrSnRK genes were designed by Primer Premier 5.0 and then detected by NCBI (). In addition, the EgrEF1α was used as a house-keeping control gene [63]. Sequence information of all primers is shown in the attached Supplementary Table S6.…”
Section: Methodsmentioning
confidence: 99%
“…The BES1/BZR1s are a large family of plant-specific transcription factors that are involved in plant growth and developmental processes, autophagy as well as response to nitrogen starvation [18,19,38]. Some prior studies have shown that the BES1/BZR1 genes are regulated by drought, salt, cold and heat stress in Brassica rapa, Eucalyptus grandis, Brassica napus and Arabidopsis [44][45][46], and accelerate drought, heat and freezing tolerance in tomato or Arabidopsis [32][33][34][35], implying that BES1/BZR1 genes participate in the osmotic stress response. In our study, the ZmBES1/BZR1-5 gene also responds to salt and drought stress in maize (Figure 1), which may be related to the cis-acting elements of its promoter [23].…”
Section: Discussionmentioning
confidence: 99%